Mapping Maqāṣid Sharia Models in Islamic Economics: A Scoping Review of Literature (2018-2022) - Muttaqin, Aris Anwaril; Samsudin, Muhammad Adib; Salleh, Ahmad Dahlan; Ahmad, Azlin Alisa; Hawa, Nabila Nurul (El-Qist: Journal of Islamic Economics and Business (JIEB), 2025)
Maqāṣid Sharia is a foundational epistemological framework for developing Islamic economics. Despite increasing scholarly attention, prior studies have inadequately mapped the diversity of Maqāṣid Sharia models employed in the discipline. This study aims to address that gap through a scoping literature review of publications from 2018 to 2022 indexed in Scopus and Web of Science, identifying the primary models applied by researchers. The analysis reveals four dominant conceptualizations: maṣlaḥah and mafsadah, kulliyāt al-khams, contemporary maqāṣid, and ḥifẓ al-māl. While the overarching term "Maqāṣid Sharia" is prevalent, the application of its methodological elements—particularly the maqāṣid framework (al-suba‘iyyah al-taṣawwuriyyah)—remains underutilized. This study contributes significantly to the global discourse by offering a structured map of Maqāṣid-based models in Islamic economics, thereby enhancing theoretical clarity and bridging methodological gaps. It recommends further exploration of the Maqāṣid methodology to enrich the development of Islamic economic theory, especially in areas such as economic epistemology, Islamic finance, the halal industry, and Islamic fintech. Future research should incorporate diverse language sources and extended databases to ensure broader analytical representation and to support a more globally integrated approach to Maqāṣid-oriented Islamic economic development.